Time reverse imaging for far‐field tsunami forecasting: 2011 Tohoku earthquake case study. Issue 22 (22nd November 2015) - Hossen, M. Jakir; Cummins, Phil R.; Dettmer, Jan; Baba, Toshitaka
Abstract: This paper describes a new method for forecasting far‐field tsunamis by combining aspects of least squares tsunami source inversion (LSQ) with time reverse imaging (TRI). This method has the same source representation as LSQ but uses TRI to estimate initial sea surface displacement. We apply this method to the 2011 Japan tsunami, and the results show that the method produces tsunami waveforms of excellent agreement with observed waveforms at both near‐ and far‐field stations not used in the source estimation. The spatial distribution of cumulative sea surface displacement agrees well with other models obtained in more sophisticated inversions, but resolve source kinematics are not well resolved. The method has potential for application in tsunami warning systems, as it is computationally efficient and can be used to estimate the initial source model by applying precomputed Green's functions in order to provide more accurate and realistic tsunami predictions. Key Points: Precise scaling using Green's functions improves time reverse imaging of tsunami source Substantially improved, near‐real‐time source estimates when precomputed Green's functions exist Excellent ability to predict far‐field waveforms for tsunami early warning in real time